Autologus Platelet Rich Plasma (PRP) in Vitro Fertilization Antagonist Protocol Caused Homeobox A 10 (HOXA10) Expression in the Endometrium of Wistar Strained Rats Higher Than Without Autologous PRP - A.A.N. Anantasika A.A.N. Anantasika; Putu Doster Mahayasa; I Nyoman Bayu Mahendra; I Gede Mega Putra; Kadek Fajar Marta; D.P.G. Jananuraga Maharddhika (Syntax Corporation Indonesia, 2023)
Endometrial receptivity is highly correlated with the implantation rate, whereby in Indonesia, the implantation rate among in vitro fertilisation programs is still low, around 19.3%. Antagonist ovarian stimulation protocol can disrupt physiological endocrine milieu by the presence of supra-physiological levels of estrogen and progesterone, both of which are thought to indirectly affect the expression of adhesion molecule cells. Homeobox A 10 (HOXA10) is among one of the biomarkers used to assess endometrial receptivity. The role of HOXA10 is critical during the stage of endometrial development and embryo implantation, both in mice and human. This molecule is thought to work optimally by administering autologous platelet rich plasma (PRP) to the damaged endometrium. The aim of this study was to prove that administration of PRP in an antagonist protocol HOXA10 expression in the endometrium of Wistar rats higher than without PRP. This research was an experimental study. The design for this study was randomized posttest only controlled group, using female Wistar-strain rats type. A total of 40 Wistar rats whose ovary were stimulated by the GnRH antagonist protocol were divided into 2 groups, 20 rats as intervention group in which PRP administration was done and 20 rats as control group. It was found that during the study, there was no significant difference between intervention and control group regarding age and body weight of the Wistar rats, both at the start and at the end of the study. The results of HOXA10 H-score in the intervention group was 3.15 (2.86-3.52) and in the control group was 1.68 (1.43-2.18) (p <0.05). Administration of PRP to ovarian stimulation with an antagonist protocol showed significantly higher expression of endometrial HOXA10 in Wistar rats than without PRP administration.